The Notre Dame arc and the Taconic orogeny in Newfoundland - van Staal, C.R.; Whalen, J.B.; McNicoll, V.J.; Pehrsson, S.; Lissenberg, Cornelis Johan; Zagorevski, A.; van Breemen, O.; Jenner, G.A. (Geological Society of America, 2007)
The Taconic orogeny in Newfoundland consisted of three accretionary events (Taconic 1, 2, and 3). Taconic 1 is represented by ca. 495 Ma, west-directed obduction of the infant-arc Lushs Bight oceanic tract (510–501 Ma) onto the peri-Laurentian Dashwoods microcontinent. Subduction is inferred to have initiated at a spreading center abandoned during an inboard ridge jump responsible for separation of Dash-woods from Laurentia and opening of the Humber seaway. Clogging of the subduction zone by Dashwoods forced subduction to step back into the Humber seaway. Inception of the new subduction zone led to formation of the ca. 490 Ma Baie Verte oceanic tract. Closure of the Humber seaway formed the Notre Dame arc (489–477 Ma) built on Dashwoods and the coeval Snooks Arm arc built on the Baie Verte oceanic tract. Sea-way closure led to collision (Taconic 2) between the arcs and Laurentia, which caused significant shortening of the Notre Dame arc. After a magmatic gap of 7–10 m.y., the Notre Dame arc records a voluminous flare-up of predominantly tonalite magmatism (464–459 Ma) during the waning stages of Taconic 2. Magmatism overlaps with deformation and includes both arc and non-arc-like tonalite. This flare-up was related to break-off of the oceanic lithosphere of the downgoing slab. The rapidly upwelling asthenosphere that replaced the broken-off slab induced melting in the subarc mantle and arc infrastructure. Taconic 3 is represented by 455–450 Ma accretion of a peri-Laurentian arc that had formed after the ca. 480 Ma initiation of west-directed subduction in the Iapetus Ocean outboard of the Dashwoods microcontinent.